Informasi Prospektus dalam Penetapan Harga IPO - Martalia Widianti; Mohamad Fany Alfarisi; Rida Rahim (SAFE-Network, 2023)
This study aims to analyze the effect of shariah-compliant status, institutional investor involvement and shareholder retention on IPO prices in concumer cyclicals and non-cyclicals companies conducting Initial Public Offerings (IPOs) listed on the Indonesia Stock Exchange in 2007-2021, with control variables underwriter reputation, leverage and profitability. From the results of testing the hypothesis using multiple regression analysis of the STATA 17 program, it was found that shariah compliant-status had no significant positive effect on IPO prices, institutional investor involvement had no significant positive effect on IPO prices, and shareholder retention had a significant positive effect on IPO prices. Maenwhile, the control variable underwriter’s reputation has a significant positive effect on the IPO price, leverage has a insignificant positive effect on the IPO priceand profitability has an insignificant positive effect on the IPO price.